Spillable Semisolid Contents of Cystic Ameloblastoma Habour Tumour Cells - Mark C. Nwoga (International Journal of Medicine and Health Development)
Background: Ameloblastoma is a cystic jaw tumor and often contains tumor fluid, blood clots, semisolid cheesy, or gelatinous materials. The histologic demonstrations of tumor invasion of the cystic contents by ameloblastoma cells have not been reported in African and western literature. The high recurrence rate of ameloblastoma has often been attributed to tumor spills during surgery. Objective: To assess for the presence of tumor cells in the semisolid contents of cystic ameloblastoma. Materials and Methods: This is a 10-year (August 2013 to July 2023) retrospective study of excisional specimens of ameloblastoma with cystic cavity contents of either blood clot, gelatinous, or cheesy materials at a tertiary health institution in Enugu, Nigeria. Results: Thirty-one resected specimens were documented with semisolid materials of blood clots, gelatinous, or cheesy materials. The male-to-female ratio, mean age, and mean duration were 1:1.7, 20.4 ± 6.6 years, and 42.0 ± 26.5 months, respectively. The specimens were all from the posterior mandible (100.0%), and 87.5% of the tumors were of the solid ameloblastoma type based on histologic study. Gelatinous material (50.0%) had the most frequent semisolid cystic content. Microscopic examination of the semisolid cavity contents demonstrated plexiform infiltrative tumors, islands, neoplastic cystic linings, stromal stellate cells, and inflammatory cells in 50% of the semisolid cystic content (blood clots, gelatinous, and cheesy materials). Conclusion: Ameloblastoma cells often invade semisolid cystic materials and could contribute to recurrences when spilled into tissues.